The impacts of cash transfers on mental health and investments: Experimental evidence from Mali - Hidrobo, Melissa; Karachiwalla, Naureen; Roy, Shalini (Elsevier, 2023)
Stress and cognitive burden associated with poverty constrain decision- making regarding investments in the future, which can in turn perpetuate poverty. We exploit the randomized roll-out of Mali's national cash transfer program to estimate its impact on measures of psychological and emotional well-being, time preferences, and cognitive function among households’ primary decision-makers. We find that receiving transfers reduced decision-makers’ self-reported stress and worry, as well as improved their self-esteem. The program did not affect measures of cognitive function but led to a modest increase in a measure of patience. Consistent with reduced stress, improved self-esteem, and increased patience, the program also increased investments in productive assets. Results suggest that, in addition to cash transfers providing the economic resources to support investments in the future, they may also build psycho-social well-being for supporting these investments.